2020
DOI: 10.1080/1343943x.2020.1829490
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating crops/weeds in an upland rice field from UAV images with the SLIC-RF algorithm

Abstract: In this study, we propose a method for discriminating crops/weeds in upland rice fields using a commercial unmanned aerial vehicles (UAVs) and red-green-blue (RGB) cameras with the simple linear iterative clustering (SLIC) algorithm and random forest (RF) classifier. In the SLIC-RF algorithm, we evaluated different combinations of input features: three color spaces (RGB, hue-saturation-brightness [HSV], CIE-L*a*b), canopy height model (CHM), spatial texture (Texture) and four vegetation indices (VIs) (excess g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 81 publications
1
27
0
1
Order By: Relevance
“…The low variability in precision of ExHSV, coupled with the ability to refine sensitivity in two colour spaces suggests it is a better option for large-scale weed detection in environments where weeds are large and green. Similarly, Kawamura et al, (2021) found combining HSV and ExG features improved performance of a machine learning model over other models trained on HSV alone. Using ExG instead of NExG in the composite ExHSV algorithm may be advantageous based on the results presented here, however, Woebbecke et al, (1995a) found non-normalized RGB chromatic coordinates to be highly variable, resulting in poorer performance.…”
Section: Performance Of Colour-based Weed Detection Algorithmsmentioning
confidence: 85%
“…The low variability in precision of ExHSV, coupled with the ability to refine sensitivity in two colour spaces suggests it is a better option for large-scale weed detection in environments where weeds are large and green. Similarly, Kawamura et al, (2021) found combining HSV and ExG features improved performance of a machine learning model over other models trained on HSV alone. Using ExG instead of NExG in the composite ExHSV algorithm may be advantageous based on the results presented here, however, Woebbecke et al, (1995a) found non-normalized RGB chromatic coordinates to be highly variable, resulting in poorer performance.…”
Section: Performance Of Colour-based Weed Detection Algorithmsmentioning
confidence: 85%
“…Another study [94] used classification algorithms based on the RF for weed extraction and unsupervised classification with the K-means algorithm to estimate weeds in non-weed areas. The simple linear iterative clustering algorithm and RF classifier had discriminated rice and weeds with better performance using hue-saturation-brightness than RGB and CIE-L*a*b consumer-grade UAV images, as shown by Kawamura et al [95]. The images from Canon S110 NIR (green, red, near-infrared) on UAV were also classified by Reis et al [42] by combining RF and maximum likelihood algorithms.…”
Section: Algorithms and Classification Techniques For Weed Mappingmentioning
confidence: 93%
“…These are typical steps to acquire RGB images captured by UAV remote sensing: (1) pre-flight planning, (2) flight and image acquisition and (3) post-processing and indices or dataset extrapolation [44]. However, when preparing the images for machine learning algorithms, the processing steps are different depending on the research's objective [45][46][47]. The advantage of using this sensor is that radiometric and atmospheric calibration are not required, unlike multispectral and hyperspectral images [41].…”
Section: Rgb Sensormentioning
confidence: 99%